Microclima, desenvolvimento e qualidade de uvas ‘Isabel precoce’ em diferentes sistemas de condução em Santa Tereza do Oeste – PR - Miranda, Jakelynye de (2018)
Several factors are the determinants for the success of viticulture among them the climatic conditions in the producing regions. The vine because it is a plant of treping habit requires a system of support and conduction, this arrangement of the canopy influences the interception of solar radiation, temperature relative humidity, consequently, interferes in its cycle and in Qualitative characteristics of the fruits. Therefore, the objective of this study was to verify the influence of the microclimatic variables on the agronomic behavior and physicochemical and phytochemical characteristics of ' Isabel Precoce ' grapes conducted in different conduction systems in the west of Paraná. The experiments were conducted at the Instituto Agronômico do Paraná in the Santa Tereza D'Oeste city, using the cultivar Isabel precoce under rootstock ' IAC 766 Campinas ', conducted in the Dual Descending and Geneva Double Curtain Trainning System. The experimental design in randomized blocks, with four replications of four plants. The evaluations were performed during the 2017/2018 harvest, being determined: phenological stages, characterization of thermal requirements, temperature and humidity at the time of production of clusters, photosynthetically active radiation intercepted, efficiency of interception and absorbed fraction of photosynthetically active radiation, leaf area index, leaf surface area, chlorophyll index, number of branches and clusters by branches, yield and estimated yield. After harvesting, the fruits were classified as standard and out-of-pattern clusters, subsequently subjected to physicochemical characterization: Curl Mass, bunch length, number of berries, mass of berries and swallow, solid content Soluble, titratable acidity, PH, soluble solids/titratable acidity ratio. The phytochemical characterization performed was as follows: phenolic compounds, flavonoids, and antioxidant activity by DPPH and Abts methods. The experimental design adopted for physicochemical characterization was in a 2x2 factorial scheme (two conduction systems x two classifications) with four replications, each one represented by a bunch. For phytochemical characterization the experimental design in randomized blocks, with four replications of 500g each. The cultivar Isabel Precoce showed similar agronomic behavior in both conduction systems during the productive cycle (pruning production-harvesting), as well as for the characteristics of chemical and phytochemical quality. The Geneva Double Curtain Trainning System presented a higher leaf area index and consequently there was a greater interception of solar radiation, as well as the fraction and efficiency of the absorbed radiation, when compared with the double descending Spredeira system. Due to the climatic conditions that occurred during the beginning of the sprouting and during the flowering phase, it provided disuniformity in the shoots thus extending the harvest period, as well as the production of clusters with physical characteristics outside the Isabel Precoce culture pattern. In this sense, it is concluded that the conduction systems in studies did not influence the agronomic characteristics of the cultivar Isabel Precoce during the 2017/2018 harvest.